From Childhood to Adulthood: The Trajectory of Damage in Patients With Juvenile‐Onset Systemic Lupus Erythematosus. Issue 11 (26th September 2017) - Lim, Lily S. H.; Pullenayegum, Eleanor; Lim, Lillian; Gladman, Dafna; Feldman, Brian; Silverman, Earl
Abstract : Objective: To determine the longitudinal damage trajectory of patients with juvenile‐onset systemic lupus erythematosus (SLE), and to identify baseline and disease course predictors of damage trajectory. Methods: This is a retrospective inception cohort. Longitudinal pediatric‐age data were obtained from a juvenile‐onset SLE research database, while adult‐age data were obtained from either a research database or patients' charts. Baseline factors were tested as predictors. Time‐varying factors were lagged 6–24 months before a visit for testing their predictive effects. The longitudinal damage trajectory was modeled using a weighted generalized estimating equation. Results: This study cohort consisted of 473 subjects, with followup to 26 years. A total of 65% of patients were ages >18 years at last followup. Cataracts (14%), avascular necrosis (10%), and osteoporosis (5%) were the most common items of damage. Two patients had myocardial infarctions. Baseline features, self‐reported ethnicity (Afro‐Caribbean), earlier time periods of diagnosis, and the presence of a life‐threatening major organ manifestation (lupus nephritis class III–V, cerebrovascular accidents, major organ vasculitis, pulmonary hemorrhage, or myocarditis), were associated with greater damage. Throughout the disease course, an acute confusional state, lupus headache, and fever predicted subsequent increases in the damage trajectory. A higher prednisone dose and exposure to cyclophosphamide also predicted subsequent increases in the damage trajectory. Antimalarial exposure was protective against an increase in damage trajectory. Conclusion: Patients with juvenile‐onset SLE accrue damage steadily into adulthood. Baseline factors predict greater damage and/or influence the evolution of the damage trajectory. Additionally, SLE clinical features and therapies during the course of disease predict additional changes in the damage trajectory.